Celebration of Free Will and Liberation in The Sun also Rises - Thapa, Mangal (Dhaulagiri Journal of Contemporary Issues, 2025)
The paper examines the female character named Ashley Brett as a character enjoying her free will and liberating subjectivity in the novel The Sun also Rises by Ernest Hemingway. Set in the context of world wars and lost generation, the novel blurs the subjectivity of woman as feminine and of man as masculine figure. The gender boundary between masculine and feminine subjectivity is blurred as women in emerging time of modernity breaks the traditional gender roles. The research has used textual analysis as research method where relevant lines are extracted and interpreted with theoretical insights of feminism. The methodology for this research is feminism where the ideas of Butler and Beauvoir are used. Butler’s idea of gender as becoming and Beauvoir’s ideas of second sex are used in this paper. As shown in the novel, Brett’s affair with Robert, Mike, Romero, the Count and other men nightclub shows that she feels happy to do what her heart says to her, and she enjoys her ‘free will’ and liberating impulse. A group of men met her, they follow her. She is also known as Lady Ashley in the night club. She is a titled British aristocrat, Robert Cohn is immediately attracted to Brett, but she does not respond at first and leaves the club with Jake. This strong determination is a feature of new woman. The paper concludes that women’s subjectivity in modern time is beyond the confinement set by a society. The research implies that modern new women enjoy liberating self.